2013
DOI: 10.1159/000346239
|View full text |Cite
|
Sign up to set email alerts
|

Magnet Removal and Reinsertion in a Cochlear Implant Recipient Undergoing Brain MRI

Abstract: Background: Recent advances in cochlear implants (CIs) and in magnetic resonance imaging (MRI) techniques have led to increasing numbers of implanted patients who have undergone brain MRIs for various reasons. This paper first describes the surgical procedure for removing the magnet before an MRI and its subsequent reinsertion immediately afterwards in a CI recipient. Method: After the administration of local anesthesia, the magnet was removed by a surgical incision made along the posterior margin of the recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…33,34 If the patient needs more than 1 MRI, the removed magnet can be replaced with a titanium plug and a new magnet can be placed when the patient has obtained all necessary MRIs. 33,34…”
Section: Resultsmentioning
confidence: 99%
“…33,34 If the patient needs more than 1 MRI, the removed magnet can be replaced with a titanium plug and a new magnet can be placed when the patient has obtained all necessary MRIs. 33,34…”
Section: Resultsmentioning
confidence: 99%
“…While aspects of CI magnet movements with potential CI damage or harm to the patients during or after MR scans are discussed elsewhere [ 23 ], the present human cadaver study analyzed diagnostic usefulness, artifacts and image quality of acquired MR brain series after cochlear implantation before and after magnet removal using a 1.5T and a 3T MR scanner. A previous report documented that CI devices with internal magnet removal are safe for 1.5T MR systems [ 24 ]. If the patient needs more than one MR examination the explanted magnet can be replaced with a titanium spacer and a new magnet can be placed when the patient has obtained all necessary MRIs [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous report documented that CI devices with internal magnet removal are safe for 1.5T MR systems [ 24 ]. If the patient needs more than one MR examination the explanted magnet can be replaced with a titanium spacer and a new magnet can be placed when the patient has obtained all necessary MRIs [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 6 This often necessitated separate surgical intervention with magnet removal and replacement, which puts the device at high risk for damage or infection. 7 8 Recently there has been a push for securement with an external compression device for cochlear implants (CIs) that contain an internal magnet, alleviating the need for separate surgical procedure. Gubbels and McMenomey (2006) examined 16 cadaver heads with Nucleus 24 CI, in which they demonstrated that without proper securement 14 of the 16 had moderate to severe displacement of the magnetic device while undergoing MRI.…”
Section: Discussionmentioning
confidence: 99%